2009
DOI: 10.1007/s00431-009-0967-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke (ETS) and respiratory health in children

Abstract: Environmental tobacco smoke (ETS) is a major risk factor for poor lung health in children. Although parental smoking is the commonest source of ETS exposure to children, they are also exposed to ETS in schools, restaurants, public places and public transport vehicles. Apart from containing thousands of chemicals, the particle size in the ETS is much smaller than the main stream smoke, and therefore has a greater penetrability in the airways of children. Exposure to ETS has been shown to be associated with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 110 publications
(109 reference statements)
2
123
1
3
Order By: Relevance
“…3,29 This is especially concerning for children, who are more vulnerable to the effects of SHS. 5,30,31 In the United States, in 2010, approximately 98% of children living with a smoker, compared to 40% not living with a smoker, had cotinine levels (a metabolite of nicotine which has a longer half-life than nicotine) above .05 ng/mL, indicating SHS exposure. 32 Cotinine levels in children are predicted by the number of cigarettes smoked inside the home.…”
Section: Effects Of Enactment Of Legislative (Public)mentioning
confidence: 99%
See 1 more Smart Citation
“…3,29 This is especially concerning for children, who are more vulnerable to the effects of SHS. 5,30,31 In the United States, in 2010, approximately 98% of children living with a smoker, compared to 40% not living with a smoker, had cotinine levels (a metabolite of nicotine which has a longer half-life than nicotine) above .05 ng/mL, indicating SHS exposure. 32 Cotinine levels in children are predicted by the number of cigarettes smoked inside the home.…”
Section: Effects Of Enactment Of Legislative (Public)mentioning
confidence: 99%
“…30,46,49,[51][52][53] All studies either reported overall significant positive effects post-legislative ban (ie, social diffusion) or no significant differences pre-and post-legislation. 20,29,[35][36][37]39,40,[46][47][48][49][50][51][52][53][54] For example, a study by Guzman et al 49 reported on cross-sectional analysis of participants surveyed before and after a statewide smoke-free law enacted in the summer of 2010 and found that participants with smoking restrictions in their homes increased significantly from 74% to 79.6% (p = .04).…”
Section: Effects Of Smoking Legislation On Home Smoking Restrictionsmentioning
confidence: 99%
“…Asthma is the commonest chronic disease in children in high and LMIC settings [3]. Environmental tobacco smoke (ETS) exposure is a well-recognized risk factor for acute and chronic respiratory illness [4]; tobacco use is the leading global cause of preventable death [5]. Despite worldwide initiatives to reduce tobacco smoking, it is estimated that up to 40% of children are still exposed to tobacco smoke [6] and approximately 6 million deaths are tobacco related with half a trillion dollars in tobacco-related economic damage [5].…”
Section: Introductionmentioning
confidence: 99%
“…Children are also at greater risk to be exposed to THS because they spend more time playing, crawling, touching contaminated surface and tend to put in non-food item in their mouth [13]. They also have higher metabolic rates and breathe in a greater amount of air per kilogram body weight, which result in more air pollutants entering their body [37].…”
Section: Discussionmentioning
confidence: 99%